2008
DOI: 10.3399/bjgp08x342237
|View full text |Cite
|
Sign up to set email alerts
|

Do general practices provide equitable access to physical activity interventions?

Abstract: Exercise referral schemes are widespread across England. National guidance emphasises the need to engage groups that are disadvantaged. AimTo examine the influence of socioeconomic deprivation on referral to, and use of, exercise referral schemes. Design of studyCross-sectional analysis of patients referred by general practices to exercise referral schemes between 2004 and 2006. SettingSix primary care trusts (PCTs) in Greater London. MethodRoutine data about patients who had been referred to exercise referral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 23 publications
8
46
5
Order By: Relevance
“…While this does not yet reach a consensus (Campbell et al 2015), extending the range of evidence considered by public health reviews may offer guidance for more targeted policy. For example, some ERS have been identified as more successful at engaging older individuals (Isaacs et al 2007;Hanson et al 2013), those living in a less deprived area (Gidlow et al 2007), or those referred from specific disease pathways (Sowden 2008;Dugdill 2005;Hanson et al 2013). At the least, guidelines should encourage attention to sub-group effects in both evaluations and by evidence users.…”
Section: Broad or Narrow: Should Policy Advocate The More Targeted Dementioning
confidence: 99%
“…While this does not yet reach a consensus (Campbell et al 2015), extending the range of evidence considered by public health reviews may offer guidance for more targeted policy. For example, some ERS have been identified as more successful at engaging older individuals (Isaacs et al 2007;Hanson et al 2013), those living in a less deprived area (Gidlow et al 2007), or those referred from specific disease pathways (Sowden 2008;Dugdill 2005;Hanson et al 2013). At the least, guidelines should encourage attention to sub-group effects in both evaluations and by evidence users.…”
Section: Broad or Narrow: Should Policy Advocate The More Targeted Dementioning
confidence: 99%
“…51 Increasing age was a factor that strongly predicted for both uptake of ERSs and adherence to the scheme in six studies. 6,23,24,38,49,51 Three studies found no such association. 18,42,47 Three studies 23,39,49 found that those most deprived were less likely to take up ERSs and two studies 23,49 found that deprivation was a predictor for not adhering to ERSs.…”
Section: Demographic Factorsmentioning
confidence: 97%
“…> 80% attendance). For four studies, [37][38][39][40] attendance at a post-ERS consultation was also required to meet the definition of adherence. The uptake of ERSs across the RCTs ranged from 35% to 100%.…”
Section: Barriers and Facilitators Of Referral Uptake And Adherence mentioning
confidence: 99%
See 1 more Smart Citation
“…). For four studies, 88,91,92,103 attendance at a post-ERS consultation was also required to meet the definition of adherence.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%